2016
DOI: 10.1099/mgen.0.000058
|View full text |Cite
|
Sign up to set email alerts
|

Pan-genomic perspective on the evolution of the Staphylococcus aureus USA300 epidemic

Abstract: Staphylococcus aureus USA300 represents the dominant community-associated methicillin-resistant S. aureus lineage in the USA, where it is a major cause of skin and soft tissue infections. Previous comparative genomic studies have described the population structure and evolution of USA300 based on geographically restricted isolate collections. Here, we investigated the USA300 population by sequencing genomes of a geographically distributed panel of 191 clinical S. aureus isolates belonging to clonal complex 8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 59 publications
5
29
1
Order By: Relevance
“…This may also provide an explanation why the prevalence of ACME − USA300 clinical isolates is still low to date. However, a recent study on evolution of USA300 has observed the increase of SCCmec − and ACME − isolates in the USA, supporting the hypothesis proposed here [35]. Furthermore, the qRT-PCR results has also confirmed that the excision is mediated by CcrAB2, because ACME excision was not observed in exSCCmec − in which the ccrAB2 genes are absent, and the excision of SCCmec is not seen in S. aureus COL because it has a premature stop codon in the ccrB gene [29].…”
Section: Discussionsupporting
confidence: 89%
“…This may also provide an explanation why the prevalence of ACME − USA300 clinical isolates is still low to date. However, a recent study on evolution of USA300 has observed the increase of SCCmec − and ACME − isolates in the USA, supporting the hypothesis proposed here [35]. Furthermore, the qRT-PCR results has also confirmed that the excision is mediated by CcrAB2, because ACME excision was not observed in exSCCmec − in which the ccrAB2 genes are absent, and the excision of SCCmec is not seen in S. aureus COL because it has a premature stop codon in the ccrB gene [29].…”
Section: Discussionsupporting
confidence: 89%
“…The pangenome of the six enterotoxigenic S. aureus was assembled and applied to highlight the genetic, metabolic, and pathogenic diversity of the species in comparison with other 29 enterotoxigenic strains. Consistent with prior studies, the numbers of new genes per genome indicated substantial intraspecific variation and overall pangenome "openness" associated with a broad niche range [110,111] but it is also a characteristic of populations that undergo frequent horizontal gene transfer [112]. In fact, S. aureus is a versatile microbe in complex microbial communities both in the environment or in a specific host, shifting between commensal or pathogenic variant [113,114].…”
Section: Discussionsupporting
confidence: 80%
“…All 56 USA300 isolates had the Susceptible 2 genotype and a penicillin-clavulanic acid MIC below the ECOFF (Supplementary Table 3). We performed a phylogenetic analysis of 580 CC8 isolates, including 485 USA300 isolates (457 MRSA, 28 MSSA) from across the USA 33,34 . All 457 of the USA300 MRSA isolates had the Susceptible 10 element (n=1) (one isolate was non-SCCmec typeable), suggesting that the majority of the USA300 population is susceptible to penicillin-clavulanic acid (Fig 4b).…”
Section: Clinical Prevalence and Epidemiologymentioning
confidence: 99%
“…The mecA promoter mutations were identified using a similar approach using in silico PCR to identify the mecA promoter region and then aligning the mecA promoter sequence and identifying mecA mutations using a custom python script. The presence of the blaZ genes was confirmed using BLAST against assemblies, this identified that 273/298 of the previously screened WGS isolates had a single copy of blaZ (excluding blaZ- Phylogenetic analysis of the CC8 isolates was carried out as previously described 33 , briefly, sequence reads were mapped using SMALT v0.7.4 (http://www.sanger.ac.uk/science/tools/smalt-0) to the S. aureus USA300_FPR3757 reference genome (accession: CP000255.1) 71 . A core genome alignment was created after excluding mobile genetic element regions, variable sites associated with recombination (detected with Gubbins ) and sites with more than 5% proportion of gaps (i.e.…”
Section: Bioinformaticsmentioning
confidence: 99%